A new matrikine‐derived peptide up‐regulates longevity genes for improving extracellular matrix architecture and connections of dermal cell with its matrix. (11th November 2019) - Leroux, R.; Ringenbach, C.; Marchand, T.; Peschard, O.; Mondon, P.; Criton, P.
Abstract: Objective: Skin extracellular matrix (ECM) is a dense and well‐organized structure produced by fibroblasts. This ECM transduces environmental mechano‐signals to cell nucleus through the integrin–actin complex, thus triggering ECM protein syntheses. The aim of this study was to discover a novel peptide, structurally related to dermal matrikines, that promotes syntheses of ECM components. Methods and results: Screening tests with 120 peptides were carried out by using normal dermal human fibroblasts (HF). As a result, one candidate of interest was isolated, the N‐Prolyl Palmitoyl Tripeptide‐56 Acetate (PP56), which increases collagen and fibronectin productions at gene and/or protein levels. Using liquid chromatography–tandem mass spectrometry (LC‐MS/MS), a recent and innovative analytical technology, in addition to more traditional techniques, it was showed that two metabolic pathways were significantly modulated: one for collagen production and one for actin. Moreover, this peptide up‐regulated the transcription of Forkhead Box O (FOXO) and sestrin messenger RNAs (mRNA), leading to production of proteins involved into longevity and more recently in collagen production. Results: Results indicated that this peptide is a potential candidate to improve ECM density and organization in a new way. Resume: Objectif: La matrice extracellulaire cutanée (MEC) est une structure dense et bien organisée produite par les fibroblastes. Cette MEC transduit les mécano‐signaux environnementaux vers le noyau de la cellule par le biais du complexe intégrine‐actine, ce qui déclenche la synthèse de protéines par la MEC. Le but de cette étude était de découvrir un nouveau peptide, structurellement apparenté aux matrikines dermiques, qui favorise la synthèse des composants de la MEC. Méthodes et résultats: Des tests de criblage avec 120 peptides ont été réalisés en utilisant des fibroblastes humains dermaux normaux (HF). Un candidat d'intérêt a été isolé, l'acétate de N‐Prolyl Palmitoyl‐Tripeptide‐56 (PP56), qui augmente les productions de collagène et de fibronectine aux niveaux du gène et / ou de la protéine. En utilisant une technologie analytique récente et innovante, la spectrométrie de masse par chromatographie liquide‐tandem (LC‐MS / MS) ainsi que des techniques plus traditionnelles, il a été démontré que deux voies métaboliques sont modulées de manière significative: une pour la production de collagène et une pour l'actine. En outre, ce peptide a régulé positivement la transcription des ARN messagers (ARNm), du facteur de transcription Forkhead Box (FOXO) et de la sestrine, conduisant à la production de protéines impliquées dans la longévité et plus récemment dans la production de collagène. Résultats: Les résultats ont indiqué que ce peptide est un candidat potentiel pour améliorer la densité et l'organisation de la MEC d'une manière nouvelle.